Prevalence of and risk factors for adverse events in Alzheimer's patients receiving anti-dementia drugs in at-home care. - Hirohisa Imai; Takuya Hirai; Ryosuke Kumazawa; Shunsaku Nakagawa; Atsushi Yonezawa; Kazuo Matsubara; Hiroyuki Nakao (PLoS ONE, 2020)
OBJECTIVE:The objective of this study was to clarify the types and prevalence of, and the risk factors for, the adverse events that occur in patients receiving anti-dementia drugs. METHODS:A questionnaire survey was conducted. The respondents were pharmacists who were dispensing anti-dementia drugs. The pharmacists responded to questions about patients who were receiving anti-dementia drugs delivered to them at home by the pharmacists. The survey questions included questions about whether or not the patients experienced adverse reactions to the drugs, about the patients' background characteristics, about the numbers of drugs the patients were taking when the pharmacists first visited the patients at home, and about the pharmacists' assessments of the appropriateness of the use of the anti-dementia drugs. RESULTS:Data were collected on 3712 patients from 1673 pharmacies in a nationwide survey. Anti-dementia drugs had been prescribed to 863 of these patients; and 801 (92.8%) of these 863 patients were 75 years of age or older, and. confirmed adverse events occurred in 170 (21%) of these 863 patients. The most common adverse event was excitation/anxiety, at 45.1%. A multivariate analysis found that polypharmacy (10 or more types of drugs per day) (P = 0.030), inappropriate use (P = 0.002), and irregular medication use (P = 0.034) were risk factors. INTERPRETATION:In order to avoid adverse events when using anti-dementia drugs, doctors and pharmacists should carefully examine the prescribing of multiple medications, assess the applicability of the use of anti-dementia drugs, and investigate how to best manage patients' drug use.